2016
DOI: 10.1039/c6tc02405j
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic halide perovskite quantum dot modified YAG-based white LEDs with superior performance

Abstract: Inorganic perovskite CsPbBr3−xIx(x= 0–3) QDs with tunable emission wavelength, narrow emission band and high quantum yields were synthesized. The fabricated CsPbBrI2QD-modified WLEDs show excellent performance in luminous efficacy, CCT and CRI, which are quite stable at an operational current as high as 350 mA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…This white‐light LED device also exhibited high CRI ( R a = 90) and CCT (6552 K). Zhou et al first used red CsPb(Br/I) 3 PQDs in a modified YAG‐based white‐light LED. Red CsPb(Br/I) 3 PQDs were mixed with PMMA in chloroform and spin‐coated on yellow‐emitting phosphor in a glass disk.…”
Section: Optical Properties and Application In Ledsmentioning
confidence: 99%
See 1 more Smart Citation
“…This white‐light LED device also exhibited high CRI ( R a = 90) and CCT (6552 K). Zhou et al first used red CsPb(Br/I) 3 PQDs in a modified YAG‐based white‐light LED. Red CsPb(Br/I) 3 PQDs were mixed with PMMA in chloroform and spin‐coated on yellow‐emitting phosphor in a glass disk.…”
Section: Optical Properties and Application In Ledsmentioning
confidence: 99%
“…b) Photographic image. c) Chromaticity coordinates in CIE diagram (Reproduced with permission . Copyright 2016, The Royal Society of Chemistry).…”
Section: Optical Properties and Application In Ledsmentioning
confidence: 99%
“…The significant progress that has been made for LHP‐NC‐based LEDs in terms of luminous efficiency has been offset by their unsatisfactory operational stability, leaving the potential of this cutting‐edge display technology uncertain. In principle, without directional ion migration driven by an applied electric field, LHP‐NCs that work as color converter under only optical excitation are significantly more stable, and all of the considerations concerning electrical features, e.g., charge carrier transport and injection, and related technical questions, e.g., film morphology and compatibility, can be neglected ( Table 2 ). Moreover, quasi‐2D LHP NCs, and especially the lead‐free halide double perovskite NCs that are difficult to use in LEDs, can be used appropriately in various applications under optical excitation.…”
Section: Lhp‐nc Color Converters For Display and Lightingmentioning
confidence: 99%
“…Because of the weak binding energy of the Cs-oleate and Pb-oleate components (∼0.5 and ∼1 eV), 49 Cs-LHQDs can be easily surface modified by other ligands by replacing the oleate from the surface. Zhou et al 64 have found that the modification of Ce 3þ ∶YAG using red-emitting CsPbBrI 2 QDs enhances its luminescence efficiency of 58 lm W −1 at the operation current of 20 mA. Similarly, due to the short-exciton recombination life time (<10 ns), CsPbBr 3 QDs have extremely high modulation bandwidth (491 MHz) over traditional phosphors which is much useful for color converting applications.…”
mentioning
confidence: 99%
“…This is due to the lower surface energy of f100g facets of Cs-LHQDs in solution. 64 Interestingly, Akkerman et al 65 adopted a similar kind of procedure and obtained 2 to 5 monolayers of nanoplatelike structures of CsPbBr 3 by the injection of acetone into the mixture. This acetone-based formation of nanoplate-like structures was observed during the synthesis of lead-based hybrid perovskite nanostructures earlier.…”
Section: Introductionmentioning
confidence: 99%